2019
DOI: 10.1186/s40478-019-0743-1
|View full text |Cite|
|
Sign up to set email alerts
|

Resistance and resilience to Alzheimer’s disease pathology are associated with reduced cortical pTau and absence of limbic-predominant age-related TDP-43 encephalopathy in a community-based cohort

Abstract: Alzheimer’s disease neuropathologic change (ADNC) is defined by progressive accumulation of β-amyloid plaques and hyperphosphorylated tau (pTau) neurofibrillary tangles across diverse regions of brain. Non-demented individuals who reach advanced age without significant ADNC are considered to be resistant to AD, while those burdened with ADNC are considered to be resilient. Understanding mechanisms underlying ADNC resistance and resilience may provide important clues to treating and/or preventing AD associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
62
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 103 publications
10
62
1
Order By: Relevance
“…cognitive or neurological decline (consistent with previous literature, e.g. Latimer et al (2019)). To annotate each node in the consensus embedding, we display their correlations with various phenotypes and covariates, as well as their enrichment for REACTOME pathways.…”
Section: Model Interpretation a Constructing And Annotating Md-ad Cosupporting
confidence: 91%
“…cognitive or neurological decline (consistent with previous literature, e.g. Latimer et al (2019)). To annotate each node in the consensus embedding, we display their correlations with various phenotypes and covariates, as well as their enrichment for REACTOME pathways.…”
Section: Model Interpretation a Constructing And Annotating Md-ad Cosupporting
confidence: 91%
“…Complex protein interactions within shared common pathways are implicated in both ageing and AD that can result in the pathologic phosphorylation, misfolding and aggregation of various proteins inclusive of TDP-43 and tau. Findings from in vitro models [46], human neuropathological studies [4,25,47] and transgenic C. elegans models [47] indicate a possible synergistic relationship between TDP-43 and tau. Therefore, we might expect to see differences in the pathological tau burden between AD/LATE-NC and AD cases, and an association between pathological tau load and LATE-NC stage.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, LATE exhibits a different neuroanatomical distribution of FTLD, and is relatively more restricted than FTLD (Kadokura et al, 2009). Autopsy showed that at least 25% of identifiable cognitive dysfunctions were associated with LATE-NC, and many subjects with LATE-NC had Aβ plaques, tauopathy, and a higher p-tau burden (Latimer et al, 2019;Nelson et al, 2019). Diagnostic and staging guidelines for LATE-NC were proposed for use during routine autopsies.…”
Section: Is It Too Late To Discover Late?mentioning
confidence: 99%